PENGARUH PANAS HIDRASI BETON DENGAN SEMEN TYPE II TERHADAP KETEBALAN ELEMEN BETON - ., Rochaeti; Endawati, Jul; Dessi Widuri, Lilian Diasti; ., The characteristics of the mixture with (Semarang State University, 2014)
The characteristics of the mixture with the heat of hydration of cement type I in the new field reads the peak temperature, the temperature of which is formed after a period of Dormant (Dormant Period) in the hydration process. The temperature difference between the core and the upper part in several monitoring results exceed 20oC thermocouple can be a trigger cracks in the long run. Overall the presence of fly ash in the concrete mix in the field is not indicated on the temperature recorded. Use of Type II cement and fly ash on the large size of the test specimen in the laboratory have not been able to lower the temperature of the mixture to the maximum, whereas for the test object with the smaller size of the maximum temperature can be met. While the temperature characteristics of the setting time with a standard test specimen (100mm x 100mm x 100mm) is not easy to be a reference to the behavior of the temperature setting time of concrete with large volume. Visually, the condition of the specimen without micro cracks, thus assuming that was taken is that the difference in temperature of the test element with the top of the core temperature is not too large (20 ° C). Such assumptions can be said is correct. With the lack of density, the temperature difference between the core layer and the top layer will not be large, because of the greater porisitas, seen from the test results PUNDIT, fast propagation rate only shows the value of 3.7 km / sec. Correlation of field test data with the data observed in the laboratory basically can not be done, because different forming materials. But the future by using cement concrete type I and fly ash by 15%, recorded temperature reaches the temperature limit (85 ° C) which can cause very large voltage difference in the concrete. The use of fly ash in greater amounts and type II cement in the test specimen in the laboratory, showing the recorded temperature reaches 68oC temperature limit, the value is lower by 19% of the maximum temperature in the field.Karakteristik panas hidrasi campuran dengan semen type I di lapangan baru terbaca pada suhu puncak, yaitu suhu yang terbentuk setelah periode Dormant (Dormant Periode) dalam proses hidrasi. Perbedaan suhu antara bagian inti dan bagian atas pada beberapa hasil monitoring thermocouple melebihi 20oC dapat menjadi pemicu retak dalam jangka panjang. Secara keseluruhan adanya fly ash dalam campuran beton di lapangan tidak terindikasi dari suhu yang tercatat. Pemakaian semen type II serta fly ash pada benda uji ukuran besar di laboratorium belum dapat menurunkan suhu campuran secara maksimal, sedangkan untuk benda uji dengan ukuran lebih kecil suhu maksimum tersebut dapat dipenuhi. Sedangkan karakteristik suhu pada setting time dengan benda uji standar (100mm x 100mm x 100mm) tidak mudah dijadikan referensi untuk perilaku suhu setting time beton dengan volume besar. Secara visual, kondisi benda uji tanpa retak mikro, dengan demikian asumsi yang kemudian diambil adalah bahwa perbedaan suhu elemen uji bagian atas dengan suhu inti tidak terlalu besar ( 20 °C). Asumsi tersebut dapat dikatakan sudah benar. Dengan kurangnya kepadatan, maka perbedaan suhu antara lapisan inti dan lapisan atas tidak akan besar, karena adanya porisitas yang lebih besar, terlihat dari hasil uji PUNDIT, nilai cepat rambat gelombang hanya menunjukkan nilai 3.7 Km/sec. Korelasi data hasil pengujian di lapangan dengan data hasil pengamatan di laboratorium pada dasarnya tidak bisa dilakukan, karena bahan pembentuk berbeda. Tetapi beton masa dengan menggunakan semen type I dan fly ash sebesar 15%, suhu terekam mencapai suhu batas (85°C) yang dapat menyebabkan perbedaan tegangan sangat besar dalam beton. Pemakaian fly ash dalam jumlah lebih banyak serta semen type II pada benda uji di laboratorium, menunjukkan suhu terekam mencapai suhu batas 68oC, nilai tersebut lebih rendah sebesar 19% dari suhu maksimum di lapangan.